Arabidopsis cryptochrome 1 promotes stomatal development through repression of AGB1 inhibition of SPEECHLESS DNA‐binding activity. Issue 11 (12th October 2021) - Cao, Xiaoli; Xu, Pengbo; Liu, Yao; Yang, Guangqiong; Liu, Minqing; Chen, Li; Cheng, Yingyu; Xu, Peng; Miao, Langxi; Mao, Zhilei; Wang, Wenxiu; Kou, Shuang; et al.
Abstract: Cryptochromes are blue light photoreceptors that mediate various light responses in plants and mammals. The heterotrimeric G‐protein is known to regulate various physiological processes in plants and mammals. In Arabidopsis, cryptochrome 1 (CRY1) and the G‐protein β subunit AGB1 act antagonistically to regulate stomatal development. The molecular mechanism by which CRY1 and AGB1 regulate this process remains unknown. Here, we show that Arabidopsis CRY1 acts partially through AGB1, and AGB1 acts through SPEECHLESS (SPCH), a master transcription factor that drives stomatal initiation and proliferation, to regulate stomatal development. We demonstrate that AGB1 physically interacts with SPCH to block the bHLH DNA‐binding domain of SPCH and inhibit its DNA‐binding activity. Moreover, we demonstrate that photoexcited CRY1 represses the interaction of AGB1 with SPCH to release AGB1 inhibition of SPCH DNA‐binding activity, leading to the expression of SPCH‐target genes promoting stomatal development. Taken together, our results suggest that the mechanism by which CRY1 promotes stomatal development involves positive regulation of the DNA‐binding activity of SPCH mediated by CRY1 inhibition of the AGB1‐SPCH interaction. We propose that the antagonistic regulation of SPCH DNA‐binding activity by CRY1 and AGB1 may allow plants to balance light and G‐protein signaling and optimize stomatal density and pattern. Abstract : Arabidopsis cryptochrome1 acts partially through ARABIDOPSIS GTP‐BINDING PROTEIN BETA 1 (AGB1), which acts through SPEECHLESS to regulate stomatal development. Cryptochrome1 and AGB1 antagonistically regulate SPEECHLESS DNAbinding activity, which may allow plants to balance light and G‐protein signaling and thus optimize stomatal density and pattern.